Metilfenidato de liberação imediata para o Transtorno do Déficit de Atenção e Hiperatividade (TDAH) em adultos: revisão sistemática - Raissa Carolina Fonseca Candido (2018)
Attention Deficit Hyperactivity Disorder (ADHD) is define as a mental health disorder characterized by three main symptoms: inattention, impulsivity and hyperactivity, which negatively affects the individual's social, academic or professional activities. Symptoms tend to decrease with aging, but may persist in adolescence and adulthood, or as well as arise only in this phase of life. Pharmacological treatment is considered the first therapeutic option for adults with moderate or severe disorder, and methylphenidate is the drug of first choice. The use of methylphenidate for the treatment of adults with ADHD is poorly documented in the literature, the available evidence is controversial and it is not possible to precisely define the benefits and harms associated with its use. This work evaluated the benefit and damage profile of immediate release methylphenidate for the treatment of ADHD in adults. For this, a systematic review of randomized controlled trials conducted according to the methodology recommended by the Cochrane for intervention studies. Eight studies involving 515 participants, aged between 18 and 60 years, were included. The doses of methylphenidate used ranged from 5 mg / day to 45 mg / day and duration of treatment between 6 weeks and 6 months. In five studies it was concluded that the use of methylphenidate in adult patients with ADHD is associated with some benefit. However, all included studies had high or undefined risk of bias and important limitations. This is due to the great heterogeneity found between the studies in the design and in the measurement of the outcome. Therefore, it is concluded that there is insufficient and conclusive evidence on the efficacy and safety of methylphenidate use in adult individuals with ADHD.